INFLUENCE OF PRODUCT QUALITY, PRODUCT INNOVATION, AND SALES PROMOTION ON CUSTOMER SATISFACTION AT LAANCBAKE MSMEs IN BANDAR LAMPUNG - Putri, Tri Oktana; Warganegara, Tri Lestira Putri (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The reason of this consider is to find out and look at how client joy at Laaancbake MSMEs in Bandar Lampung is affected by item quality, item development, and deals advancement. The statistic beneath consider in this investigate is shoppers of Laancbake MSMEs; in this way, the test measure, as evaluated by the Lemshow strategy, demonstrated that 100 respondents were required for the consider. Different direct investigation, the coefficient of assurance test, and the t test are among the quantitative methods utilized in this consider. The comes about appear that (1) Laaancbake MSMEs in Bandar Lampung’s customer satisfaction is positively and significantly impacted by product quality (2) Laaancbake MSMEs in Bandar Lampung’s customer satisfaction is positively and significantly impacted by product innovation. (3) Laaancbake MSMEs in Bandar Lampung’s customer satisfaction is positively and significantly impacted by sales promotion. (4) Laaancbake MSMEs in Bandar Lampung’s customer satisfaction is together significantly impacted by product quality, product innovation, and sales promotion.